Kanizsa-figure object completion gates selection in the attentional blink. Issue 7 (July 2019) - Chen, Siyi; Nie, Qi-Yang; Müller, Hermann J; Conci, Markus
Previous work has demonstrated that perceptual grouping modulates the selectivity of attention across space. By contrast, how grouping influences the allocation of attention over time is much less clear. This study investigated this issue, using an attentional blink (AB) paradigm to test how grouping influences the initial selection and the subsequent short-term memory consolidation of a target. On a given trial, two red Kanizsa-type targets (T1 and T2) with varying grouping strength were embedded in a rapid serial visual presentation stream of irrelevant distractors. Our results showed the typical AB finding: impaired identification of T2 when presented close in time following T1. Moreover, the AB was modulated by the T2 grouping—independently of the T1 structure—with stronger grouping leading to a decreased AB and overall higher performance. Conversely, a reversed pattern, namely an increased AB with increasing grouping strength was observed when the Kanizsa figure was not task-relevant. Together, these findings suggest that the grouping benefit emerges at early perceptual stages, automatically drawing attentional resources, thereby leading to either sustained benefits or transient costs—depending on the task-relevance of the grouped object. This indicates that grouping modulates processing of objects in time.